Endoscopic Surgery for Supratentorial Deep Cavernous Malformation Adjacent to Cortical Spinal Tract: Preliminary Experience and Technical Note - Lin, Fuxin; Li, Chunwang; Yan, Xiaorong; Wang, Dengliang; Lin, Yuanxiang; Kang, Dezhi; Jiang, Changzhen (Frontiers in Neurology, 2021)
In this study, we aimed to introduce the technical note and to explore the efficacy of endoscopic surgery combining Diffusion Tensor Imaging (DTI) navigation for supratentorial deep cerebral cavernous malformations (CCM). A prospectively maintained database of CCM patients was reviewed to identify all CCM patients treated by endoscopic surgery. The sagittal T1-weighted anatomical MRI and DTI were acquired before surgery. Endoscopic surgery was planned and performed based on preoperative DTI images and intraoperative DTI navigation. All patients were followed up more than 6 months. Motor function deficit and mRS scores were documented on follow-up. A final mRS score of 0–2 was considered a good outcome, and a final mRS score greater than 2 was considered a poor outcome. Second DTI and 3DT1 were performed at 3 months after surgery. We tracked the ipsilateral CST on pre- and postoperative DTI images. The overall mean FA values and number of fibers of tracked CST were compared on pre- and post-operative DTI images. Risk factors associated with motor deficits and poor outcomes were analyzed. Seven patients with deep CCM and treated by endoscopic surgery were enrolled in this study. The mean value of preoperative mRS was 1.5±0.98, but that score recovered to 0.86±1.22 3 months later. The mRS scores were improved significantly according to statistical analysis (p=0.012). According to the Spearman nonparametric test, only the fiber number of ipsilateral CST on postoperative DTI was significantly associated with muscle strength 6 months after surgery (p=0.032). Comparing with preoperative CST characteristics on DTI, the change of FA value (p=0.289) and fiber number (p=0.289) of ipsilateral CST on postoperative DTI was not significant. It meant that the CST was protected during endoscopic surgery. Endoscopic surgery based on DTI navigation might be an effective method to protect fiber tracts in supratentorial deep CCMs patient and improve long-term outcomes. However more studies and cases are needed to confirm our findings.